There is no such thing as a crisis: A critique of and alterative to the dominant crisis management model. (29th May 2019) - Spector, Bert
Abstract: In this Forum piece, I propose an alternative conceptual model, one that replaces the crisis event with the claim of urgency made by a leader as the focal unit of analysis. The proposed crisis‐as‐claim model insists that no claim of urgency is legitimate per se. From the perspective of the researcher, the crisis‐asclaim model reverses cause‐and effect from the event to the claim as independent variable. Finally, the crisis‐as‐claim model elides the consideration of heroic leadership so common in the crisis‐as‐event model, positioning instead leaders as claims makers always intent on advancing interests and enhancing power.